2022
DOI: 10.1002/adom.202102441
|View full text |Cite
|
Sign up to set email alerts
|

Donor Arylmethylation toward Horizontally Oriented TADF Emitters for Efficient Electroluminescence with 37% External Quantum Efficiency

Abstract: Designing thermally activated delayed fluorescence (TADF) emitters with high horizontal orientation dipole ratios (Θ//) is regarded as one of the key measures to achieve high light outcoupling efficiency and thus efficient organic light‐emitting diodes (OLEDs). Herein, donor arylmethylation is presented to construct horizontally oriented TADF emitters. Two compounds PFDMAC‐TRZ and DPFDMAC‐TRZ are designed and synthesized through Friedel‐Crafts arylmethylation of their parent TADF molecule DMAC‐TRZ with 9‐pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The AZB donor is strongly twisted about the N–C bond, with dihedral angles of 81.4(2)° and 82.5(2)° [87.7(2)°] in AZB-Ph-TRZ and AZB-TRZ , respectively (Figure ). This dihedral angle is much larger than the corresponding angle (45.1°) in an equivalent Cz-Ph-TRZ analogue and is slightly smaller than the 90° angle in the DMAC-TRZ …”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The AZB donor is strongly twisted about the N–C bond, with dihedral angles of 81.4(2)° and 82.5(2)° [87.7(2)°] in AZB-Ph-TRZ and AZB-TRZ , respectively (Figure ). This dihedral angle is much larger than the corresponding angle (45.1°) in an equivalent Cz-Ph-TRZ analogue and is slightly smaller than the 90° angle in the DMAC-TRZ …”
Section: Resultsmentioning
confidence: 60%
“…AZB-TRZ instead exhibits a broad and red-shifted CT emission at λ PL = 494 nm. In toluene, Cz-Ph-TRZ, DMAC-TRZ , and azasiline-Ph-TRZ emit at 422, 498, and ∼460 nm, respectively, all of which are red-shifted compared to the λ PL of AZB-Ph-TRZ . ,, TD-DFT calculations on the S 1 -optimized geometries predict λ PL of 472 nm ( f = 0.000) and 573 nm ( f = 0.001) for AZB-Ph-TRZ and AZB-TRZ in the gas phase, respectively, which align with these experimental results. The emission spectra of AZB-Ph-TRZ and AZB-TRZ both show typical bathochromic shifts with increasing solvent polarity (positive solvatochromism), indicating that the S 1 state is CT in nature in sufficiently polar media (Figure S23).…”
Section: Resultsmentioning
confidence: 86%
“…This dihedral angle is much larger than the corresponding angle (45.1°) in an equivalent Cz-Ph-TRZ 30 analogue, and is slightly smaller than the 90° angle in the DMAC-TRZ. 32 Scheme 1. Synthesis of AZB-Ph-TRZ and AZB-TRZ.…”
Section: Resultsmentioning
confidence: 99%
“…In toluene, Cz-Ph-TRZ, DMAC-TRZ, and azasiline-Ph-TRZ emit at 422 nm, 498 nm, and ~460 nm, respectively, all of which are red-shifted compared to the lPL of AZB-Ph-TRZ. 27,32,34 The emission spectra of AZB-Ph-TRZ and AZB-TRZ both show the typical bathochromic shift with increasing solvent polarity (positive solvatochromism), indicating that the S1 state is CT in nature in sufficiently polar media (Figure S20). Comparing the emission onset wavelengths of the structurally analogous series in more polar THF solvent (which elicits only CT emission), we identify that Cz-Ph-TRZ has the shortest wavelength (highest energy) onset at 400 nm, followed by AZB-Ph-TRZ (425 nm) and then azasilane-Ph-TRZ (450 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the (200) preferential orientation-index α 200 of the prepared films, and as observed, it practically does not present changes due to the effect of temperature increase, remaining at approximately 0.90, which shows that the orientation process was carried out from low temperatures and, once the material crystallized, the system tends to maintain that orientation. It is worth mentioning that when Pluronic F-127 acid is used, in some studies, it has been shown that it changes the size of the particles and their orientations [36][37][38][39][40][41][42][43], which is a very desirable property for luminescent films since oriented films tend to minimize the scattering of light during emission process, therefore incrementing its quantum efficiency [44,45]. On the other hand, the crystallite size does not present a significant difference with the increment in the annealing temperature, as can be observed in Table 1.…”
Section: Chemical Evolution and Structural Propertiesmentioning
confidence: 99%